SERVICE QUALITY, CUSTOMER SATISFACTION, CUSTOMER LOYALTY AND WORD OF MOUTH AT PT. VILLA MITRA SEHATI BADUNG - George Elvis Ludji Koro (Jurnal Manajemen dan Bisnis, 2014)
The purpose of this study were 1) to determine and analyze the effect of the Increasingcompetition and customers are more selective and knowledgeable require service providers toconstantly improve the quality of service. In order to improve the quality of care, it must firstbe known whether the service provided to customers had been in accordance with customerexpectations or not.The problem in this study are: The main problem as an institution that services manyof its competitors is the service provided consumer expectations if it is appropriate or not?,While the purpose of this research is to improve service quality, customer satisfaction customerloyalty in order to create word of mouth is positive. From the analysis of the data using a SEManalysis showed that the relationship between the variables affect each other positively andsignificantly.Keywords: Quality of Service, Customer Satisfaction, Customer Loyalty and Word Of Mouth